Zakres suwerenności podatkowej państw Unii Europejskiej - Sokołowski, Jerzy (The scope of tax sovereignty of the EU member states, 2006)
The article discusses tax sovereignty of the EU member stales. EU Directives impose some limitations on independent decisions concerning tax system. This refers primarily to VAT and excise taxes. Member states’ sovereignty in the sphere of direct taxation is far less limited. The author attempts to provide an answer to the question ofthe extent to which EU Directives can and should interfere with tax systems of individual member stales.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 250-255